Evaluating the Burden of Autoimmune Thyroid Disorders: Findings from Tertiary Care Facilities of Bangladesh (Journal of Dhaka National Medical College & Hospital, 2024)
Introduction: Autoimmune thyroid disorders (ATDs) like Graves' disease and Hashimoto's thyroiditis affect 2%-5% globally, yet localized data in Bangladesh are scarce. This study investigates genetic, environmental, and gender factors influencing ATD prevalence. Understanding these risks is crucial for effective management and public health strategies.Methods: This observational cross-sectional study in two major Bangladesh healthcare facilities aimed to assess the burden of autoimmune thyroid disorders. With a sample size of 73 participants, strict inclusion criteria targeted individuals likely to have ATDs—18 and above, showing suspected thyroid disorder based on Thyroid-Stimulating Hormone (TSH) values or already on thyroid medication. The study gathered comprehensive clinical data through medical record reviews, focusing on prevalence, demographics, and the correlation between TSH levels and ATDs. This design offered a snapshot of ATD prevalence and management in these Bangladeshi healthcare settings.Result: The study involved 73 participants, primarily aged between 31 and 50, with a female predominance (83.56%). The average age was 41.77 years. BMI ranged from 18.55 to 44.55, with 47.95% overweight and 27.40% at a healthy weight. The most prevalent thyroid conditions were subclinical hyperthyroidism (38.36%) and hyperthyroidism (35.62%), with an average TSH level of 12.25 micro IU/I. 30.14% tested positive for thyroid antibodies, indicative of autoimmune thyroid disorders, while 32.88% had diabetes, the most common comorbidity. Hypertension (21.92%) and dyslipidemia (9.59%) followed. Menstrual irregularities were reported by 26.03% of participants, with menopause in 28.77%. The study explored associations between thyroid status and comorbidities but found no statistically significant correlations for diabetes, hypertension, dyslipidemia, NAFLD, impaired glucose tolerance, or CKD across different thyroid statuses.Conclusion: The study highlights the high prevalence of autoimmune thyroid disorders (ATDs) in Bangladesh, particularly subclinical hyperthyroidism and hyperthyroidism, with a significant female predominance. It emphasizes the need for increased awareness and targeted screening, especially in middle-aged individuals. The study also highlights the complex interplay between ATDs and comorbid conditions.J. Dhaka National Med. Coll. Hos. 2024; 30 (02): 15-22